Podstawowe funkcje sądów kopnych na ukraińskich ziemiach od XIV do XVIII wieku - Bedrìj, Mar'ân (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is devoted to the basic functions of “kopa” courts on Ukrainian lands in 14th–18th centuries, namely the areas of their activity, through which they implemented certain socially important tasks. Investigative, judicial, executive, conciliation and law-making functions of “kopa” courts are analyzed. Investigative function performed by “kopa” courts under “hot kopa” implied pursuing criminals, inquiry and preliminary investigation of the case. Judicial and conciliation functions were realized by means of examining and deciding on the case. Executive function was expressed in the fact that “kopa” courts usually executed their own decisions. Law-making functions of “kopa” courts were manifested in the fact that as a result of their activities, changes were made to the existing legal customs as well as new ones were introduced.
Keywords: sądy kopne; funkcje sądów kopnych; ukraińskie zwyczaje prawne; historia sądów